MOF-mediated synthesis of monodisperse Co(OH)2 flower-like nanosheets for enhanced oxygen evolution reaction. (20th May 2018) - Cui, Cao; Wang, Jingyun; Luo, Zhenguo; Wang, Jin; Li, Chunxia; Li, Zhengquan
Abstract: Cobalt hydroxide in α-form (α-Co(OH)2 ) is an attractive electrocatalyst for oxygen evolution reaction (OER). Traditional preparation of α-Co(OH)2 nanosheets often leads to a packing morphology after synthesis or post electrode fabrication, which severely limits the exposure of surface active sites. In this work, we report the synthesis of a self-supported 3D flower-like structure consisting of 2D α-Co(OH)2 nanosheets through a metal-organic-framework (MOF)-mediated synthetic method. We found that the formation of MOF intermediates can produce dispersive α-Co(OH)2 nanosheets with a stable 3D hierarchical structure which can effectively avoid the packing of individual nanosheets. The developed α-Co(OH)2 nanosheets exhibit an obviously enhanced OER activity in comparison with the nanosheets prepared with traditional method. The prepared α-Co(OH)2 nanosheets have been well characterized and their formation mechanism is proposed. Graphical abstract: